Revitalization Strategy for Traditional Markets Using Market Basket Analysis (AR-MBA) And Service Quality (SERVQUAL) Approaches - Soleh, Muhamad; Hidayati, Nurul; Pamungkas, Tri Dedi (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
The rise of modern markets in Purwokerto provides benefits such as diverse shopping options and increased competition in pricing and services. However, this trend negatively impacts traditional markets, which are experiencing a decline in customers. Understanding customer behaviour and needs is essential for enhancing the competitiveness of traditional markets. The AR-MBA method analyses shopping behaviour by identifying frequent item set combinations. The findings from the AR-MBA analysis can inform business strategies, including promotions, market re-layouts, and marketing campaigns aimed at boosting sales in traditional markets. To enhance competitiveness, traditional markets must be revitalised by improving service quality. A Servqual Model analysis will assess the gap between customer expectations and the current state of these markets. This study aims to restore the vital role of traditional markets by enhancing service quality to compete effectively with modern markets. This research is important for policymakers and market managers as it provides insights that can be used to formulate effective strategies to strengthen the competitiveness of traditional markets and ensure local economic sustainability. This strategy enhances customer convenience by positioning frequently purchased items close together based on the Association Rule analysis. It encourages impulse buying, as shoppers are likelier to notice complementary products. Additionally, a sales strategy focused on bundling products can increase perceived value and motivate customers to purchase more items together, ultimately leading to higher sales and a better shopping experience. By maintaining high-performing areas while addressing gaps in service quality, traditional markets can remain strong competitors against modern retail outlets. Keywords: Traditional market, revitalise, AR-MBA, shopping behavior, Market layout, Servqual Model